IDENTIFIKASI PENERIMAAN BEASISWA DIPA MENGGUNAKAN METODE BACKWARD CHAINING - Wahyu Iskandar (Institut Bisnis Muhammadiyah Bekasi, 2021)
Scholarships are generally a provision of fees for education for students who are still actively attending lectures at a tertiary institution. With the scholarship so that it can help students to finance their needs during college. With the backward chaining method can facilitate the campus bureaucrats in determining students who are entitled to receive scholarships. Backward Chainning is a model in reverse of hypotheses, a potential or conclusion that must be proven by facts that support the hypothesis. The backward chaining model in receiving scholarships takes some data from existing variable criteria such as active lecture certificates, student cumulative achievement indexes, attaching TOEFL certificate, identity card, and curriculum vitae. Next make a decision tree from the data variables that exist and finally is implemented. The results of this study have an accuracy of 95%, which can be recommended to get the scholarship and this method can facilitate the determination of scholarship acceptance. The backward chaining method is very effective and accurate in determining DIPA scholarship recipients with an accuracy rate of 95%, making it easier for the North Sumatra state Islamic university community to select students who are eligible to receive.